The identity of Artemisia transbaicalensis (Asteraceae) - Liu, Yifan; Leostrin, Artem; Seregin, Alexey P.; Chen, Xiyang; Li, Dingyu; Li, Ang; Gao, Tiangang; Jiao, Bohan (Phytotaxa, 2025)
Artemisia transbaicalensis Leonova, a species widely accepted in important biodiversity databases, is shown to be conspecific with A. tanacetifolia Linnaeus based on the evidence from morphology and geography.